Amorphous Cobalt Boride (Co2B) as a Highly Efficient Nonprecious Catalyst for Electrochemical Water Splitting: Oxygen and Hydrogen Evolution. Issue 6 (7th January 2016) - Masa, Justus; Weide, Philipp; Peeters, Daniel; Sinev, Ilya; Xia, Wei; Sun, Zhenyu; Somsen, Christoph; Muhler, Martin; Schuhmann, Wolfgang
Abstract : It is demonstrated that amorphous cobalt boride (Co2 B) prepared by the chemical reduction of CoCl2 using NaBH4 is an exceptionally efficient electrocatalyst for the oxygen evolution reaction (OER) in alkaline electrolytes and is simultaneously active for catalyzing the hydrogen evolution reaction (HER). The catalyst achieves a current density of 10 mA cm −2 at 1.61 V on an inert support and at 1.59 V when impregnated with nitrogen‐doped graphene. Stable performance is maintained at 10 mA cm −2 for at least 60 h. The optimized catalyst, Co2 B annealed at 500 °C (Co2 B‐500) evolves oxygen more efficiently than RuO2 and IrO2, and its performance matches the best cobalt‐based catalysts reported to date. Co2 B is irreversibly oxidized at OER conditions to form a CoOOH surface layer. The active form of the catalyst is therefore represented as CoOOH/Co2 B. EXAFS observations indicate that boron induces lattice strain in the crystal structure of the metal, which potentially diminishes the thermodynamic and kinetic barrier of the hydroxylation reaction, formation of the OOH* intermediate, a key limiting step in the OER. Abstract : Cobalt boride (Co2 B) is presented as a highly efficient water splitting nonprecious catalyst for oxygen and hydrogen evolution in alkaline electrolytes. The catalyst achieves a current density of 10 mA cm −2 at as low as 1.61 VRHE and is among the best reported for cobalt‐based catalysts. Stable performance was maintained for at least 60 h during electrolysis at 10 mA cm −2 .